A rare form of dermatomyositis associated with muscle weakness and normal creatine kinase level. Issue 2 (6th February 2020) - Kwan, Christopher; Milosevic, Suzana; Benham, Helen; Scott, Ian A
Abstract : We present a case study of a 61-year-old Vietnamese woman who presents with features of dermatomyositis (DM), including Gottron's papules, heliotrope rash, cutaneous ulcers, generalised weakness and pain, and weight loss with normal levels of creatine kinase (CK). She demonstrated features of interstitial lung disease and subsequently tested positive for anti-melanoma differentiation-associated gene 5 and anti-small ubiquitin-like modifier 1 activating enzyme antibodies, which belong to a DM subtype known as clinically amyopathic dermatomyositis and do not present with raised CK. She received standard treatment for DM, including oral prednisolone, hydroxychloroquine, mycopheonlate and topical betamethasone. The treatment successfully reversed skin changes; however, the patient remained generally weak and unable to carry out her activities of daily living.